Evaporation and condensation of flash boiling sprays impinging on a cold surface. (1st March 2021) - Xiao, Di; Qiu, Shuyi; Hung, David; Li, Xuesong; Nishida, Keiya; Xu, Min
Abstract: Flash boiling spray is considered a potential solution for addressing spray impingement related issues such as pool fire caused by spray-wall interactions, in addition to its benefit of improving fuel-air mixing in engine cylinders. In comparison to typical sub-cooled spray impingement, flash boiling spray impingement can be affected by more complicated heat transfer and the mass transfer processes, including fuel vapor condensation near the wall when the temperature is very low. This work aims to investigate the wall film formation when flash boiling sprays impinge on a cold surface. Laser-induced exciplex fluorescence (LIEF) technique was used in this investigation to separate the fluorescent signals from the liquid phase and the gas phase during spray impingement. The simultaneous measurement of the thickness and temperature distributions of the wall film on a transparent plate were conducted, and corresponding heat and mass transfer of the film were analyzed. Generally, flash boiling impingement on cold surface would deposit less film mass on the wall than sub-cooled sprays, however it was still much larger than flash boiling spray impinging on room temperature plate. It was found that under flash boiling conditions, the combination of fine droplets and a large quantity of vapor impinged on the wall to form much less film. As wall temperature decreased, evaporation suppression and condensation effects became increasingly significant to dominate the wall film formation and development.